At the river - Elliot, Kendra (Elliot, Kendra. Columbia River., 2024)
"While investigating the murder of a true crime podcaster, FBI Special Agent Mercy Kilpatrick and her police chief husband uncover a connection to a decades-old cold case kidnapping"--